Effect of processing parameter on chemical composition of clitoria ternatea extract / Nur Lina Syahirah Mustapa, Mahirah Muhammad Rosli and Nurul Izah Juhari - Mustapa, Nur Lina Syahirah; Muhammad Rosli, Mahirah; Juhari, Nurul Izah
Clitoria Ternatea is an herbaceous plant that contain many bioactive compounds for the health benefits. The processing parameter in extraction method is crucial to obtain its bioactive compound which contribute to its antioxidant properties. Therefore, this study was conducted to determine the effect of different processing parameter on the chemical composition which is the total antioxidant compounds. Three different processing parameters were investigated which are different temperature of oven drying (40°C, 50°C, 60°C, 70°C) and the detection method (GCMS, HPLC, UHPLC, FCR); different drying method (oven, microwave, air, freeze) and the determination method (GCMS, HPLC, FTIR, LCMS); and different types of solvent (methanol, ethanol, hexane, acetone) and the detection method (HPLC, GCMS, UHPLC, LCMS). This study was carried out by using Taguchi method in Minitab software 14. The results were measured by observing the signal to noise ratios to obtain which processing parameter is significant to the total antioxidant compounds. Other than that, by considering the P-value and the delta value the most significant effect can be determined. The results indicate that the temperature of oven drying is more significant than its detection method towards the total antioxidant. The optimum temperature of oven-drying for the extraction of C. Ternatea flower obtained is at 70C. Furthermore, the effect of different drying method gives more impact on the antioxidant activity especially air drying. The different uses of solvent give a significant effect that can influence the antioxidant activity during extraction. Using methanol as a solvent will preserve the bioactive compound in C. Ternatea extract. In a nutshell, the processing parameters which are temperature, drying method, and solvent will affect the total antioxidant compounds of the C. Ternatea extract.